Pro-Calcitonin, Erythrocyte Sedimentation Rate and C - reactive Protein in Predicting Diabetic Foot Ulcer Characteristics; a Cross Sectional Study - Hadavand, Fahimeh; Amouzegar, Atefeh; Amid, Hessam (Archives of Academic Emergency Medicine, 2019)
Introduction: Considering the importance of early diagnosis of diabetic foot ulcers and its complications, this study aimed to evaluate the accuracy of erythrocyte sedimentation rate (ESR), C - reactive protein (CRP), and pro-calcitonin (PCT) in predicting the ulcer class, osteomyelitis, and peripheral arterial disease (PAD). Methods: This cross-sectional study was performed on 200 consecutive patients suffering from diabetic foot ulcer who were referred to Infectious Disease Ward. The levels of PCT, ESR, and CRP were measured for all patients and the screening performance characteristics of each marker in predicting the ulcer class, osteomyelitis, and PAD was calculated. Results: The levels of PCT, ESR and CRP were significantly higher in patients with class IV foot ulcer compared to those with class III ulcers (p<0.001). Patients with evidence of osteomyelitis had significantly higher level of PCT, ESR and CRP. The best cutoff points of PCT, ESR and CRP in predicting osteomyelitis were 0.35 ng/ml (86.1% sensitivity, 45.3% specificity), 56.5 mm/hours (95.8% sensitivity, and 50.0% specificity) and 44 mg/ml (90.3% sensitivity, 57.0% specificity), respectively. The presence of PAD was significantly associated with increased levels of the three biomarkers. The best cutoff values for PCT, ESR and CRP in predicting PAD were 0.45 (70.8% sensitivity, 71.7% specificity), 61.5 (83.3% sensitivity, 52.0% specificity) and 49 (83.3% sensitivity, 63.8% specificity), respectively. Conclusion: Based on the findings of the present study, although the accuracy of PCT, ESR, and CRP in predicting the severity of diabetic foot ulcers was fair, increase in the three parameters can predict the occurrence of osteomyelitis and PAD following diabetic food development with good accuracy and acceptable sensitivity.